Temperature Effect of Extraction on Physicalochemical Properties Glukomanan Origin Amorphophallus muelleri Blume - Nunung Harijati; Serafinah Indriyani; Retno Mastuti (Natural B, Journal of Health and Environmental Sciences, 2013)
This study had aims to find the optimum temperature for the extraction of the glucomannan with good physicochemical characters . The method that used for extraction was the stirring method according varies temperatures (35-55-75oC), followed by centrifugation with speed 1500 rpm for 30 minutes at temperatures 25°C. Glucomannan was coagulated using 95% isopropyl alcohol. Parameters that observed included glucomannan yield,  ash and water content, flour color, lightness of glukomanan as well as calcium oxalate contents. The results showed that glucomannan extraction  at 55°C gave optimal results (63.1% per dry weigh of tuber), followed  by 52.2% and 39.91%  for extracted temperature 35°C and 75°C respectively. There was no different significantly in color of glucomannan flour in between temperature which had L value 25.17; 27.23 and  26.37 correspond with  extraction temperature 35°C, 55 °C, and 75°C. The calcium oxalate content of all treatment was 0.03-0,11% . The treatments also gave 1.17-2.00% ash content, 4.6-5.53% water content and 49.5-2654.5 Cp of viscosity.